2017 Winter Simulation Conference (WSC) 2017
DOI: 10.1109/wsc.2017.8247790
|View full text |Cite
|
Sign up to set email alerts
|

History of uniform random number generation

Abstract: Random number generators were invented before there were symbols for writing numbers, and long before mechanical and electronic computers. All major civilizations through the ages found the urge to make random selections, for various reasons. Today, random number generators, particularly on computers, are an important (although often hidden) ingredient in human activity. In this article, we give a historical account on the design, implementation, and testing of uniform random number generators used for simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 162 publications
(159 reference statements)
0
45
0
Order By: Relevance
“…It was inspired by a problem that arises in hybrid navigation systems that use both GPS and dead-reckoning sensors [40]. The third experiment, involving a step change in the parameters of a signal generator, was an analogue to a problem that may arise in evaluating multiple stream random number generators [41], where we may detect and evaluate the probability of changes in the parameters of those generators. The fourth experiment was the detection of the disappearance of noise.…”
Section: The Design Of the Experimentsmentioning
confidence: 99%
“…It was inspired by a problem that arises in hybrid navigation systems that use both GPS and dead-reckoning sensors [40]. The third experiment, involving a step change in the parameters of a signal generator, was an analogue to a problem that may arise in evaluating multiple stream random number generators [41], where we may detect and evaluate the probability of changes in the parameters of those generators. The fourth experiment was the detection of the disappearance of noise.…”
Section: The Design Of the Experimentsmentioning
confidence: 99%
“…The sequence is normal (or ∞-distributed) if it is k-distributed for any k ≥ 1. Borel called normal to base b a real number from the interval (0, 1) whose expansion in base b is normal sequence, and showed that almost all real numbers are normal to any base (with respect to the uniform measure) [1,2]. It is interesting that the construction of ∞-distributed sequence in an explicit form was first achieved by Champernowne in 1933 [3], who proved that the sequence 0 1 2 ...9 10 11 12 ... 99 100 101 102 ...…”
Section: Introductionmentioning
confidence: 99%
“…Later, many ∞-distributed sequences were described and investigated in numerous papers (see for review [4]). Many researchers suppose that fractional parts of π, e, and √ 2 and some other "mathematical" constants are normal, but it is not proven [2,5]. On the other hand, for π empirical counting over several billions of its digits suggests that this might be true (see [5,6]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, p. 84+) that such post-processing provides a new PRNG at minimal cost which is 2.5 times faster than the PRNGs which pass the whole TestU01 [16]. Moreover, it is worth noticing that most of the classical PRNGs [18,19] do not pass the TestU01.…”
Section: Introductionmentioning
confidence: 99%